2016
DOI: 10.1002/cne.24077
|View full text |Cite
|
Sign up to set email alerts
|

5‐hydroxymethylcytosine marks postmitotic neural cells in the adult and developing vertebrate central nervous system

Abstract: The epigenetic mark 5-hydroxymethylcytosine (5hmC) is a cytosine modification that is abundant in the central nervous system of mammals and which results from 5-methylcytosine oxidation by TET enzymes. Such a mark is suggested to play key roles in the regulation of chromatin structure and gene expression. However, its precise functions still remain poorly understood and information about its distribution in non-mammalian species is still lacking. Here, the distribution of 5hmC was investigated in the brain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…As a reader for both 5mC and 5hmC (Mellén et al, 2012; Spruijt et al, 2013; Diotel et al, 2017), MeCP2 (methyl-CpG-binding protein 2) has similar affinity to 5hmC and 5mC (Mellén et al, 2012). However, the 5hmC level is negatively correlated with MeCP2 abundance.…”
Section: Where Are 5hmc Bases?mentioning
confidence: 99%
See 1 more Smart Citation
“…As a reader for both 5mC and 5hmC (Mellén et al, 2012; Spruijt et al, 2013; Diotel et al, 2017), MeCP2 (methyl-CpG-binding protein 2) has similar affinity to 5hmC and 5mC (Mellén et al, 2012). However, the 5hmC level is negatively correlated with MeCP2 abundance.…”
Section: Where Are 5hmc Bases?mentioning
confidence: 99%
“…Global detection of 5hmC has been carried out in human, mouse, zebrafish, and Xenopus (Globisch et al, 2010; Munzel et al, 2010; Chen and Riggs, 2011; Jin et al, 2011; Song et al, 2011; Szulwach et al, 2011a,b; Almeida et al, 2012; Han et al, 2016; Diotel et al, 2017). These studies showed that the dynamics and abundance of 5hmC are cell type-dependent and developmentally regulated.…”
Section: Where Are 5hmc Bases?mentioning
confidence: 99%
“…Loss of demethylation by active mechanisms should also be considered, such as the activation of the GADD45B demethylase in the DG cells during adult neurogenesis [49] or the transformation of 5-methylcytosine (5-mC) into 5-hydroxymethylcytosine (5-hmC) by enzymes of the TET family [50]. 5-hmC is enriched in adult neurons compared to NSPCs of the SVZ in the mouse developing brain and colocalize with MeCP2 and with the active chromatin histone modification H3K4me2 in mouse neurons [51]. Another mechanism by which CpG methylation results in transcriptional silence is by binding to methyl-CpG-binding proteins that recruit several chromatin remodelling proteins.…”
Section: Main Textmentioning
confidence: 99%
“…5mC subsequently declines as migration begins from the upper limits of the VZ and through the IZ and enters a second cycle of up-regulation in the upper cortical layers as maturing neurons prepare for synaptogenesis. 5hmC, which functions as a bivalent or activating epigenetic mark (Chen, Damayanti, Irudayaraj, Dunn, & Zhou, 2014; Diotel et al, 2016; Resendiz, Chen, Öztürk, & Zhou, 2013), appears as differentiation proceeds and peaks when neurons are specified. In the VZ, where cortical proliferation (Ki67+) and neurogenesis progress and in SVZ where neural specification begins (Tbr2+ cell bodies), 5mC is prominent in the cells with mostly ellipsoidal-shaped nuclei, while 5hmC weakly appears in a subpopulation of the VZ and SVZ.…”
Section: Discussionmentioning
confidence: 99%